Analysis on the Impact of English Teachers’ Continuing Professional Development (CPD) on Teaching Ability: A Case Study of Applied Undergraduate Colleges in Henan Province - LI, QIN; Mohammed, Lubna Ali (Journal of Ecohumanism, 2024)
Background and purpose: With the rapid development of higher education in China and the rise of applied undergraduate colleges, the continuing professional development (CPD) of English teachers is becoming increasingly important. This study aims to explore in depth the impact of CPD on the teaching ability of English teachers in applied undergraduate colleges in Henan Province, analyse teachers’ attitudes towards and participation in CPD and its effectiveness, and examine the role of demographic characteristics and teacher creativity in this process. Method: A mixed research method was used, combining quantitative and qualitative analysis. A questionnaire survey was conducted among 294 English teachers (with a 85.5% response rate) from 10 applied undergraduate colleges in Henan Province. The questionnaire included aspects such as teachers’ background information, frequency of CPD participation, attitudes towards CPD, and perceived teaching ability. In addition, 20 semi-structured interviews and four focus group discussions (24 participants in total) were conducted to obtain more in-depth qualitative data. Descriptive statistics, correlation analysis and multiple regression analysis were performed using SPSS software, and Hayes’ PROCESS macro was used to analyse moderated effects. Main results: Teachers had a generally positive attitude towards CPD (mean score 4.587/5), but institutional support was lower (mean score 3.326/5). There were significant differences in the frequency of participation in CPD activities: professional reading had the highest participation rate (65.9% participated frequently or very frequently), while industry-university cooperation had the lowest (only 22.8%). CPD had a positive impact on all aspects of teaching ability, especially technology integration (72.5% reported a significant or transformative impact). Multiple regression analysis showed that the frequency of CPD participation was the strongest predictor of perceived teaching ability (β = 0.458, p < 0.001), followed by attitude towards CPD (β = 0.265, p < 0.001). Teacher creativity significantly moderated the relationship between CPD participation and teaching competence (B = 0.087, p = 0.026), indicating that teachers with higher creativity are better able to translate their CPD experiences into teaching practice. Heavy workload (65.6%) and insufficient time (59.5%) were the main barriers to CPD participation. Technical training (64.9%) and reflective practice groups (59.2%) were the most popular types of CPD activities. Conclusions and recommendations: The findings of this study highlight the important role of CPD in improving the teaching capacity of English teachers in applied undergraduate institutions, while also revealing the challenges in the current implementation of CPD. Recommendations for educational institutions are as follows: Increase institutional support for CPD to create more time and resources for teachers to participate in CPD. Design a diversified CPD programme with a balanced mix of activities, with a particular focus on industry-university collaboration and action research. Focus on technical training and reflective practice to improve teachers’ digital literacy and innovation capabilities. Develop personalised CPD pathways that take into account teachers’ career stages, educational backgrounds and career aspirations. Explore more flexible CPD formats, such as microlearning modules or blended learning approaches, to overcome time and workload barriers. This study provides an empirical basis and practical guidance for the CPD of English teachers in applied undergraduate colleges in Henan Province and even in China, which is of great significance for improving teaching quality and student learning outcomes.